Daya Tarik Wisata Taman Hutan Raya Ir.H Djuanda Sebagai Tempat Wisata Dan Tempat Tracking Yang Mempunyai Sejarah Bagi Wisata - Azmi Noer Afifah; Muhammad Bintang Alief Al Daffa (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
This research was conducted to explain the tourist attractions in Ir. Forest Park. H. Djuanda in Bnadung City. This research has the main objective, namely to attract the younger generation to be interested in traveling and exercising while studying or seeing history firsthand. This research explores tourist attractions in the park and their historical values, with a focus on attractions that can attract the interest of the younger generation. The problem with this research is the lack of interest of the younger generation in places that have historical value and also about the diversity or recreational potential of these places. Meanwhile, the method used is to analyze the place so as to create a strategy that can attract the attention of the younger generation. The theory used is a marketing strategy which includes a comprehensive plan that provides direction regarding the activities that will be carried out to achieve a goal within the company through advertising, promotional programs, sales and distribution. The results of this research discuss the important role of the marketing strategy of Ir. Forest Park. H Djuanda is a tourist attraction that has beautiful diversity and historical value